Benchmark-Driven Investments in Emerging Market Bond Markets : Taking Stock - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2020)
This paper reviews the role of benchmark-driven investments in EM local bond markets. We provide an overview of how key EM bond benchmark indices are constructed, how they affect the behavior of investment funds, and what are the likely implications for capital flows and policy-making. Several methods are presented suggesting that the amount of assets benchmarked against widely followed EM local-currency bond indices have risen fivefold since the mid-2000s to around USD 300 billion. Our review suggests that the benefits of index membership may be tempered by portfolio outflow risks for some countries. This is because benchmark-driven investments may increase the importance of external factors at the expense of domestic factors, raising the risks of outflows unrelated to recipient country fundamentals. Some countries may be disproportionately exposed to these risks, reflecting the way the indices are constructed.